Amino-functionalized MOFs with high physicochemical stability for efficient gas storage/separation, dye adsorption and catalytic performance. Issue 47 (21st November 2018) - Fan, Weidong; Wang, Xia; Xu, Ben; Wang, Yutong; Liu, Dandan; Zhang, Ming; Shang, Yizhu; Dai, Fangna; Zhang, Liangliang; Sun, Daofeng
Abstract : Three versatile amino-functionalized In III /Al III /Zr IV -MOFs with high-physicochemical stability for gas storage/separation, water purification and catalysis. Abstract : A major goal of metal–organic framework (MOF) research is to adjust the structure and function for specific applications. It is highly desirable to develop new multifunctional MOF materials for selective guest molecule storage/separation and catalysis. Recent advances in the synthesis of MOFs have created new opportunities in this direction. Although many multifunctional MOFs have been synthesized to explore different applications, it is still a challenge to construct MOFs with high physicochemical stability for specific applications. In addition, most of the MOFs only have a microporous structure, which is not conducive to the transportation of substances and the entry of macromolecules, thus limiting the applications of these materials in macromolecular adsorption. Herein, we present three amino-functionalized In III /Al III /Zr IV -based MOFs with high physicochemical stability for multifunctional performances. The pore size of these MOFs varies from a few angstroms to the nanometre scale, and their specific surface areas and pore volumes gradually increase with the change of nodes. Further studies reveal that these MOFs are promising candidates as storage mediums for hydrogen (H2 ) and as separation agents for the selective removal of (C3 H n –C2 H n ) from natural gas (NG). The mesoporous Zr-MOF can effectively enrich dye molecules to purify water, and the adsorption dynamics of a series of organic dyes shows that there are no size and charge-selective effects for the adsorption process. Furthermore, the catalytic efficiency and mechanism of Knoevenagel condensation reactions have also been studied in detail. Overall, the three versatile amino-functionalized MOFs highlight the advantages of metal–organic frameworks for designing host materials tailored for applications in hydrogen (H2 ) storage, light hydrocarbon adsorption/separation, water purification, and catalysis.